Activation of Wnt5a‐Ror2 signaling associated with epithelial‐to‐mesenchymal transition of tubular epithelial cells during renal fibrosis. (12th June 2013) - Li, Xin; Yamagata, Kaoru; Nishita, Michiru; Endo, Mitsuharu; Arfian, Nur; Rikitake, Yoshiyuki; Emoto, Noriaki; Hirata, Ken‐ichi; Tanaka, Yoshiya; Minami, Yasuhiro
<x xml:space="preserve">Abstract</x> Activation of Wnt5a‐Ror2 signaling has been shown to be associated with epithelial‐to‐mesenchymal transition (EMT) of epidermoid carcinoma cells via induction of matrix metalloproteinase‐2 (MMP‐2). Because EMT has also been implicated in the progression of tissue fibrosis, we examined the possible association of Wnt5a‐Ror2 signaling with renal fibrosis. Here, we show that expression of Wnt5a and Ror2 is induced in a damaged mouse kidney after unilateral ureteral obstruction (UUO) treatment. Immunofluorescent analysis showed that Ror2 expression is clearly induced in tubular epithelial cells during renal fibrosis, and these Ror2‐expressing cells also express Snail and vimentin, markers of mesenchymal cells, suggesting that Ror2 might be induced in epithelial cells undergoing EMT. We also found that MMP‐2 expression is induced at Ror2‐positive epithelium adjacent to significantly disrupted tubular basement membrane (TBM). Interestingly, reduced expression of MMP‐2 is detected at epithelium in damaged kidneys from Ror2+/− mice compared with those from wild‐type Ror2+/+ mice. Importantly, extents of TBM disruption are apparently reduced in damaged kidneys from Ror2+/− mice compared with those from wild‐type mice. Collectively, these findings indicate that activation of Wnt5a‐Ror2 signaling in epithelial cells undergoing EMT may play an important role in disrupting TBM via MMP‐2 induction during renal fibrosis.